Land use/land cover dynamics in the northern watershed of lake Tana: implications for water quality - Engdaw, Flipos; Fetahi, Tadesse; Kifle, Demeke (Frontiers in Environmental Science, 2024)
Rapid population growth-induced urbanization, industrialization, deforestation, settlement expansion and habitat destruction are significant drivers of LU/LC change at global scale. The uncontrolled LU/LC change, specifically in developing countries like Ethiopia, poses significant environmental threats to water quality, biodiversity, and ecosystem services. This study, therefore, examined LU/LC trends in the Lake Tana catchment, Ethiopia from 1993 to 2022, analyzed the impact of changes on water quality and identified major driving factors for policy input. ArcGIS software and Landsat imagery were employed toproduce maps for 10 years. Water quality data were obtained from primary and secondary sources from 2002 to 2022. The relationship between LU/LC changes and water quality was examined using Pearson’s correlation and principal component analysis (PCA). Results revealed significant (p < 0.05) spatio-temporal variations in water quality parameters, with almost all parameters showing a substantial increase from 2002 to 2012 and some declined in 2022. LU/LC changes were categorized into six classes with an overall accuracy and Kappa coefficient of 92.2% and 0.86%, respectively. Various LU/LC classes were highly correlated with a particular water quality parameter. Settlement and crop land expansion were positively correlated with nutrients such as (NH3− + NH4+-N), NO3-N, SRP, and TP. Forestation was positively correlated with good water quality such as DO and pH, while they were negatively correlated with temperature, EC, SRP, and NO3-N demonstrating a strong linkage between LU/LC and water quality. These findings therefore, validate the significance of prioritizing LU/LC changes for sustainable water quality and ecosystem service improvement in the Lake Tana catchment.